General Election as a Means of Creating a Clean, Good and Authorized Government - Wardana, Surya Kusuma (Law Research Review Quarterly, 2019)
General Election is a means to make it happen sovereignty of the people in the government of the Republic of Indonesia, which is based on Pencasila, as mandated in the 1945 Constitution of the Unitary State of the Republic of Indonesia. Therefore, general elections need to be held in a higher quality with the widest possible participation of the community / people and be carried out based on direct principles. public, free, confidential, honest, and fair. The general election to elect members of a representative institution must be able to guarantee the principles of representation, accountability, and legitimacy. Meanwhile, the general elections for the President and Vice President are held in a democratic and civilized manner with the widest possible participation of the people which are carried out based on direct, general, free, confidential, honest, and fair principles. the president and the general election law for members of DPR, DPD, DPRD (Province / City / Regency), such as the principles of representation, accountability, and legitimacy as well as the principles of honesty and fairness, all of which are intended to be able to realize a clean, good, and authoritative government.